Immunological disorders and malignancies in five young brothers. Issue 4 (April 1977) - Purtilo, D T; Riordan, J A; Deflorio, D; Yang, J P; Sun, P; Vawter, G
Abstract : Five brothers of from 6 to 18 years of age experienced immunological or neoplastic disorders during an 8-year interval. 2 boys succumbed to glioblastoma multiforme, another to metastatic carcinoma, and the 2 surviving brothers had a histiocytic lymphoma and idiopathic thrombocytopenia purpura, respectively. The mother of the boys was healthy, but her twin sister died in utero of birth defects. We suggest that an intrinsic cellular defect inherited from their mother rendered the boys vulnerable to oncogenesis.